Combination Therapies in Chronic Myeloid Leukemia for Potential Treatment-Free Remission: Focus on Leukemia Stem Cells and Immune Modulation - Mu, Hui; Zhu, Xiaojian; Jia, Hui; Zhou, Lu; Liu, Hong (Frontiers in Oncology, 2021)
Although tyrosine Kinase Inhibitors (TKI) has revolutionized the treatment of chronic myeloid leukemia (CML), patients are not cured with the current therapy modalities. Also, the more recent goal of CML treatment is to induce successful treatment-free remission (TFR) among patients achieving durable deep molecular response (DMR). Together, it is necessary to develop novel, curative treatment strategies. With advancements in understanding the biology of CML, such as dormant Leukemic Stem Cells (LSCs) and impaired immune modulation, a number of agents are now under investigation. This review updates such agents that target LSCs, and together with TKIs, have the potential to eradicate CML. Moreover, we describe the developing immunotherapy for controlling CML.